Topical Vancomycin Reduces Surgical-Site Infections After Craniotomy: A Prospective, Controlled Study. Issue 4 (18th December 2017) - Mallela, Arka N; Abdullah, Kalil G; Brandon, Cameron; Richardson, Andrew G; Lucas, Timothy H
Abstract: BACKGROUND: Surgical-site infections (SSIs) are an important cause of morbidity and mortality in neurosurgical patients. Topical antibiotics are one potential method to reduce the incidence of these infections. OBJECTIVE: To examine the efficacy of topical vancomycin applied within the wound during craniotomy in a large prospective cohort study at a major academic center. METHODS: Three hundred fifty-five patients were studied prospectively in this cohort study; 205 patients received 1 g of topical vancomycin powder in the subgaleal space while 150 matched control patients did not. Patients otherwise received identical care. The primary outcome variable was SSI rate factored by cohort. Secondary analysis examined cost savings from vancomycin usage estimated from hospital costs associated with SSI in craniotomy patients. RESULTS: The addition of topical vancomycin was associated with a significantly lower rate of SSI than standard of care alone (0.49% [1/205] vs 6% [9/150], P = .002). Based on the costs of revision surgery for infections, topical vancomycin usage was estimated to save 1367 446 per 1000 craniotomy patients. No adverse reactions occurred. CONCLUSION: Topical vancomycin is a safe, effective, and cost-saving measure to prevent SSIs following craniotomy. These results have broad implications for standard of care in craniotomy.